Analysis of Patient Safety Culture at Semen Padang Hospital Indonesia - Yona Ladyventini; Isniati; Wihardi Triman (HM Publisher, 2023)
Background: Hospitals have a role and function to provide integrated health services for patients as consumers of health services. When providing services to patients, hospitals must pay attention to quality and safety. This study aimed to find out the patient safety culture that has been built at Semen Padang Hospital in 2022. Methods: This study uses an approach mixed methods research with a design sequential explanatory, namely research that uses a combination of quantitative and qualitative methods simultaneously (quantitative-qualitative). The subjects of this study were employees of Semen Padang Hospital, with as many as 81 respondents for quantitative data and 11 respondents for qualitative data. Measurement of patient safety culture using the MaPSaF instrument (Manchester patient safety framework) in the form of filling out the MaPSCAT questionnaire (Manchester patient safety culture assessment tool). This questionnaire consists of 10 dimensions with a total of 24 questions and is equipped with in-depth interview data. Results: Data collection was carried out using the MaPSCAT instrument on 10 dimensions of patient safety culture, 6 dominant dimensions were at the proactive level, namely the dimension of overall commitment to continuous improvement (1st dimension), the dimension of system error and individual responsibility (3rd dimension), the dimension of incident evaluation and best practices (5th dimension), effective learning and change (6th dimension), communication about patient safety issues (7th dimension) and staff education and training dimension (9th dimension). Conclusion: The safety culture at Semen Padang Hospital is generally at a proactive level. This indicates that the hospital places priority on improving patient safety and is carried out on an ongoing basis. A system that is integrated and comprehensive has a wide scale, involved stakeholders, and an evidence-based approach.